Nas trilhas das batalhas de MC's: pelo direito humano de viver a cidade - Palhano, Giovanna Silva (2023)
This dissertation aims to reflect on the meanings of the right to the city from the practical appropriation and forms of uses that young people involved in the Hip Hop MC's Battles of the metropolitan region of the city of São Luís-Ma make of their spaces in urban centers, observing their educational experiences and the condition of these young people as subjects and conductors of political projects. The study starts from the experiences of two Batalhas, Batalha Itinerante and Batalha do MB, both carried out by young residents of the peripheries that happen without fail in public and common spaces and bring together some aesthetic expressions of Hip Hop culture, such as improvisational duels, duels and break-dancing presentation, poetry performance, DJing etc. We question how young people construct meanings in relation to this event, and in which aspects their aesthetic expressions are related to an education in human rights. We had as objectives to describe the dynamics of organization and duels of the battles of MC's, to discuss the youth category allied to the spatial dimension and to reflect on the educational experiences and meanings of the right to the city in the dynamics of these meetings. The theoretical framework of the study was situated between the critical theory of human rights (FLORES, 2009; SANTOS, 2014; SOUSA JUNIOR, 2019) of urban sociology and sociology of youth (LEFEBVRE, 2001; CASSAB 2021; PERALVA, 1997) and education in/for human rights (CANDAU, 2008; BRANDÃO, 2009). The adopted methodology was the ethnography GEERTZ, 1978; MAGNANI, 2002) which enables the use of the research subjects' narratives as a necessary path for the construction of data, in which it is possible to resort to a set of techniques such as observation, field diary, maps, cartographies, photographs, interactions, aiming at bring the set of signifiers in terms of which events, facts, actions and contexts are produced, perceived and interpreted. We conclude that the right to the city Achado na Rua is the right to freedom of occupation and production of spaces. The city as a public space through the experiences of the Battles of MC's gains a real meaning and the aesthetic and political expressions for the right to inhabit it becomes itself an educational process, of construction, learning and formation of the subjects who participate in them.